2001
DOI: 10.1074/jbc.m011687200
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domain of Syntaxin 1A Is Critical for Cytoplasmic Domain Protein-Protein Interactions

Abstract: Assembly of the plasma membrane proteins syntaxin 1A and SNAP-25 with the vesicle protein synaptobrevin is a critical step in neuronal exocytosis. Syntaxin is anchored to the inner face of presynaptic plasma membrane via a single C-terminal membrane-spanning domain. Here we report that this transmembrane domain plays a critical role in a wide range of syntaxin proteinprotein interactions. Truncations or deletions of the membrane-spanning domain reduce synaptotagmin, ␣/␤-SNAP, and synaptobrevin binding. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 60 publications
2
34
0
1
Order By: Relevance
“…However, because of its mis-localization (data not shown), the H3 domain by itself could not induce EAAC1 inhibition without the assistance of the transmembrane domain (Kasai and Akagawa, 2001;Lewis et al, 2001). In fact, our data show that, at least in the presence of the H3 and transmembrane domains, syntaxin 1A associated with EAAC1 on the cell surface, leading to the reduction of its surface expression and the inhibition of glutamate transport.…”
Section: Discussionmentioning
confidence: 68%
“…However, because of its mis-localization (data not shown), the H3 domain by itself could not induce EAAC1 inhibition without the assistance of the transmembrane domain (Kasai and Akagawa, 2001;Lewis et al, 2001). In fact, our data show that, at least in the presence of the H3 and transmembrane domains, syntaxin 1A associated with EAAC1 on the cell surface, leading to the reduction of its surface expression and the inhibition of glutamate transport.…”
Section: Discussionmentioning
confidence: 68%
“…Recently, it has been reported that the transmembrane domain of syntaxin 1 is critical for its proper interaction with other proteins (Lewis et al, 2001). Actually, Sly1 did not have an effect on the binding after membrane solubilization by Triton X-100 in our cell free system (data not shown).…”
Section: Discussionmentioning
confidence: 69%
“…Pull-down assays GST-pull down assays were performed as described previously using 80 µg bead-immobilized GST-C2ABC or GST-C2DEF (Lewis et al, 2001;Dong et al, 2003). In brief, SNARE complexes were formed by incubating 50 µM t-SNARE heterodimer and 50 µM synaptobrevin 2 overnight at 4°C.…”
Section: Turbidity Measurementsmentioning
confidence: 99%
“…Gels were digitized using a scanner and processed using Illustrator. Whole brain lysate immunoprecipitation assays were performed using rat brain detergent extracts that were prepared as described previously (Chapman et al, 1995;Lewis et al, 2001). 1% Triton X-100 was used for solubilization.…”
Section: Point Mutations Disrupt the Function Of Otoferlin C2 Domainsmentioning
confidence: 99%